Edukasi ASI Eksklusif Melalui Media Infografis Meningkatkan Pengetahuan Ibu Balita - Lisa Amelina; Rini Harianti (JURNAL RISET GIZI, 2024)
One of the reasons for the high wasting rate currently is the low coverage of exclusive breastfeeding. Inappropriate understanding by mothers regarding exclusive breastfeeding can also affect the growth of toddlers. The population in this study were toddlers in Mulyasejati Village, the subjects were 35 toddlers from Posyandu Cempaka 2 and 9. The sampling technique used accidental sampling. The pre-test and post-test data were then processed using IBM SPSS Statistics version 22.0 and Google Spreadsheet software. The pre-test and post-test scores were calculated using the Guttman scale with a correct answer worth 1 and an incorrect answer worth 0. The normality test used the Shapiro-Wilk test followed by the Wilcoxon test because the data distribution was not normally distributed. Based on anthropometric measurements, it was found that 33 (94.3%) toddlers had good nutritional status based on BMI/U and BW/TB, and 27 (77.1%) based on normal weight BW/U. The level of knowledge of mothers of toddlers regarding exclusive breastfeeding, the majority of mothers of toddlers have good knowledge. Knowledge of mothers of toddlers regarding exclusive breastfeeding is shown by p-value= 0.012 (p0.05). In conclusion, there is an influence of providing education using infographic media on increasing the knowledge of mothers of toddlers with a p-value of more than 0.05.